Biochemical Description of the Systemic Inflammatory Response in infants after Severe Birth Asphyxia - S.S. Ovcharenko; N.M. Mezhirova; G.D. Kravtsova (Zaslavsky O.Yu., 2014)
This article presents the results of a study of biochemical indicators of systemic inflammatory response in infants after severe birth asphyxia. In a group of 34 newborns there were determined the indicators of inflammation: interleukin-6, interleukin-1β, interleukin-4, tumor necrosis factor α and the level of weighted average molecules. The study revealed that the course of systemic inflammatory response in recovered infants was caused by the activation of anti-inflammatory cytokine interleukin-4, which may have prevented the progression of systemic inflammatory response and the development of endogenous intoxication. The course of systemic inflammatory response in died neonates was characterized by activation of anti-inflammatory as well as pro-inflammatory cytokines with the simultaneous development of endogenous intoxication and abrupt inhibition of cytokine synthesis against the progression of endogenous intoxication on the 7th day of life.